REPOSISI ETIKA PEMASARAN DAN PENGUATAN KEUANGAN SYARIAH DALAM TRANSFORMASI DIGITAL KOPERASI SYARIAH DI INDONESIA - Nasrul Amanu (Jurnal Adab dan Peradaban Islam, 2025)
The digital transformation has fundamentally reshaped the operational landscape of Sharia cooperatives, particularly in marketing ethics, financial governance, and institutional interaction. This study examines the repositioning of Islamic marketing ethics and the strengthening of Sharia-compliant financial practices amid the rapid digitalization of Sharia cooperative services in Indonesia. Employing a qualitative approach through a systematic literature review, the study analyzes scholarly works published within the last five years concerning Islamic marketing ethics, fintech, cooperative governance, data security, and digital financial inclusion. The findings reveal that Islamic marketing ethics must be redefined to align with the dynamics of the digital environment, particularly regarding information transparency, data protection, and algorithmic integrity. Furthermore, strengthening Sharia-compliant finance requires integrating technologies that not only enhance service efficiency but also ensure Sharia compliance through digital auditing, data-driven risk management systems, and automated financial processes. Digital transformation presents substantial opportunities for Sharia cooperatives to expand outreach, increase accountability, and reinforce members’ business ecosystems. However, structural constraints such as low digital literacy, uneven infrastructure, and weak governance remain persistent challenges. This study concludes that balancing technological innovation with Sharia principles is essential for fostering a visionary, ethical, and sustainable transformation of Sharia cooperatives.